Time Perception is a Focal Symptom of Attention-Deficit/Hyperactivity Disorder in Adults - Weissenberger, Simon; Schonova, Katerina; Büttiker, Pascal; Fazio, Raffaele; Vnukova, Martina; Stefano, George B; Ptacek, Radek (Medical science monitor, 2021)
Attention-Deficit/Hyperactivity Disorder (ADHD) is classically associated with symptoms that include inattentiveness, hyperactivity, and impulsivity together with a variety of other observable externalized symptoms. ADHD has also been associated with specific internalized cognitive symptoms, including restlessness and emotional impulsivity. This disorder has been recognized as a lifelong condition and can be recognized by a variety of unique cognitive phenomena. In addition to the frequently ignored affective symptoms exhibited by individuals diagnosed with ADHD, problems with time perception have been noted, although these are considered to be secondary issues. Temporal shifts in cognitive processing, however, may be at the very root of ADHD-related symptoms, given the importance of coordinated signal translation in the construction of behavior. In this review, we consider the evidence that suggests that differences in time perception are a central symptom in adults with ADHD. Some of these differences include the feeling of time moving faster, which causes difficulties in prospective time tasks and inaccuracies in time estimation tasks. We analyze the literature from both neurological and psychological perspectives and include an assessment of tools that can be administered via computer to measure time perception. We also suggest several computer-based methods that might be used to address problems with time perception in both children and adults. We strongly recommend the inclusion of ADHD symptoms associated with time perception in the next revision of the Diagnostic and Statistical Manual of Mental Disorders (DSM) published by the American Psychiatric Association.
Keywords: kognitivní poruchy; emoce; Impulsive Behavior; Attention; Child; Emotions; dítě; Adult; Prospective Studies; dospělí; impulzivní chování; průzkumy a dotazníky; pozornost; Attention Deficit Disorder with Hyperactivity; hyperkinetická porucha; úzkost; lidé; Humans; Cognition Disorders; Surveys and Questionnaires; Anxiety; Time Perception; vnímání času; prospektivní studie